From “Human-to-Human” to “Human-to-Non-human” – Influence Factors of Artificial Intelligence-Enabled Consumer Value Co-creation Behavior - Wen, Haitao; Zhang, Lulu; Sheng, Ao; Li, Mingda; Guo, Bingfeng (Frontiers in Psychology, 2022)
The emergence of artificial intelligence (AI) has changed traditional methods of value co-creation. Diverging from traditional methods, this study discusses the influencing factors of AI-supported consumer value co-creation from the perspective of human-to-nonhuman interactions. This study adopts the stimulus–organism–response framework with consumer engagement (CE) as the intermediary to explore the impact of consumers’ personal subjective factors, community factors, and perceptions of AI technology on their value co-creating behaviors. Data were collected from 528 respondents from the Huawei Huafen Club, Xiaomi BBS, Apple China Virtual Brand, Micromobile Phone, and Lenovo communities. SPSS Amos software was used for statistical analysis, revealing that perceived personalization, autonomy, community identity, trust in AI, and self-efficacy are motivational factors that have significant effects on consumer value co-creation behaviors, in which CE plays a significant intermediary role. Our study contributes to the literature on consumer value co-creation supported by AI technology. We also offer important insights for developers of AI-enabled products and service managers.